A river of words : the story of William Carlos Williams - Bryant, Jen. 1960- (Eerdmans Books for Young Readers, 2008)
In this picture book biography of poet William Carlos Williams, Jen Bryant's engaging prose and Melissa Sweet's stunning mixed-media illustrations celebrate the amazing man whose poems about ordinary, everyday things will inspire young readers to create poems of their own.